HUBUNGAN ANTARA DAYA LEDAK TUNGKAI, KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA TANGAN TERHADAP KEMAMPUAN LAY-UP SHOOT - Nurjamal Nurjamal; Ruslan Ruslan; Hendry Ismawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2019)
This study aims to determine the relationship between leg explosive power, wrist flexion and hand eye coordination on shoot lay-up ability. This type of research is a type of descriptive research. The research variables consisted of independent variables namely leg explosive power, wrist flexion and hand eye coordination, while the dependent variable was shoot lay-up ability. The population in this study were all students of the Health and Recreation Physical Education Study Program FKIP Mulawarman State University with a sample of 30 people. The data analysis technique used was correlation and regression analysis using the SPSS Version 22.00 system at a significance level of 95% or (α) = 0.05. Proceeding from the results of data analysis, concluded that: 1) There was a relationship between leg explosive power and lay-up shoot capability, as evidenced by the calculated r value (ro) = 0.680 (P = 0.000 <α: 0.05); 2) There is a correlation between wrist flexing and shoot lay-up ability, it is proven that the value of r count (ro) = 0.734 (P = 0.000 <α: 0.05); 3) There is a correlation between eye hand coordination and shoot lay-up ability, it is proven that the value of r count (ro) = 0.689 (P = 0.000 <α: 0.05); and 4) There is a relationship between leg explosive power, wrist flexion and hand eye coordination to the shoot lay-up ability, as evidenced by the calculated r value (ro) = 0.768 (P = 0.000 <α: 0.05).